The Language of Airline Slogans: A Linguistics Analysis - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2018)
To promote themselves, airlines do not only serve better but also have slogans to be known as their identities. The use of slogans is unique and appealing if they are seen from linguistics point of view. The objectives of this research are to find out the Syntactic categories, semantic claims and Speech acts that used by 35 Airlines Slogans in five continents. To know the answers, the researcher used Content analysis and finds that Syntax category which mostly used by Airlines slogans around the world is phrase, majority airlines slogans take benefits from the use of we are different and unique claim, and the most frequent speech act that used by airline slogan is representative.